Food-safety hazards in the pork chain in Nagaland, North East India: Implications for human health - Fahrion, Anna S.; Jamir, L.; Richa, K.; Begum, S.; Rutsa, V.; Ao, S.; Varijakshapanicker, Padmakumar; Deka, Ram Pratim; Grace, Delia (MDPI, 2014)
Pork occupies an important place in the diet of the population of Nagaland, one of the North East Indian states. We carried out a pilot study along the pork meat production chain, from live animal to end consumer. The goal was to obtain information about the presence of selected food borne hazards in pork in order to assess the risk deriving from these hazards to the health of the local consumers and make recommendations for improving food safety. A secondary objective was to evaluate the utility of risk-based approaches to food safety in an informal food system. We investigated samples from pigs and pork sourced at slaughter in urban and rural environments, and at retail, to assess a selection of food-borne hazards. In addition, consumer exposure was characterized using information about hygiene and practices related to handling and preparing pork. A qualitative hazard characterization, exposure assessment and hazard characterization for three representative hazards or hazard proxies, namely Enterobacteriaceae, T. solium cysticercosis and antibiotic residues, is presented. Several important potential food-borne pathogens are reported for the first time including Listeria spp. and Brucella suis. This descriptive pilot study is the first risk-based assessment of food safety in Nagaland. We also characterise possible interventions to be addressed by policy makers, and supply data to inform future risk assessments.